Surface finishing and tool wear in single point diamond turning of chemical vapour deposited tungsten carbide hard coatings - Micallef, Christian; Zhuk, Yuri; Aria, Adrianus Indrat (Elsevier, 2022)
Precision-engineered components which operate in demanding conditions often require the application of hard coatings such as tungsten carbide (WC) to improve their functional properties. Following the coating deposition process, a surface finishing or machining operation is often required to correct the sizing or achieve adherence to geometrical tolerancing and surface finish requirements. Single point diamond turning (SPDT) is a widely used ultraprecision machining technique for the fabrication of high-end engineering components made up of ductile materials, making it a desirable technique as a post-coating machining or finishing process. In this study the machinability of hard CVD W/WC coatings with a hardness of 1120 ± 15 HV and a thickness of 100 μm using SPDT was investigated. Here we report the results of axial and transverse turning using a cutting speed of 600 rpm and feed rates of 1 and 5 μm respectively. Experimental results show that an Ra of 0.2 μm is achieved with a diamond tool having a 0.5 mm nose radius. Significant tool wear was observed at the rake/flank edge of the diamond tool due to the coating's hardness. Surface and cross-sectional analysis of the samples' machined areas revealed presence of adhesive and abrasive wear. The occurrence of material pile-up due to tool loading on the surface of the coating was investigated through the indentation technique which demonstrated the occurrence of material deformation contributing to the overall surface roughness.
Keywords: Diamond turning; SPDT; Tungsten carbide; Tool wear; Plastic side-flow